Ecological niche divergence associated with species and populations differentiation in Erythrophleum (Fabaceae, Caesalpinioideae) - Anaïs-Pasiphaé Gorel; Jérôme Duminil; Jean-Louis Doucet; Adeline Fayolle (Plant Ecology and Evolution, 2019)
Background and aims – The isolation of populations inside forest refugia during past climate changes has widely been hypothesized as a major driver of tropical plant diversity. Environmental conditions can also influence patterns of diversity by driving divergent selection leading to local adaptation and, potentially, ecological speciation. Genetic and phylogenetic approaches are frequently used to study the diversification of African tree clades. However, the environmental space occupied by closely related species or intra-specific gene pools is barely quantified, though needed to properly test hypotheses on diversification processes.Methods – Using species distribution models, we determined the bioclimatic constraints on the distribution of closely related species and intra-specific gene pools. Our study model, Erythrophleum (Fabaceae – Caesalpinioideae), is a tropical tree genus widespread across Africa, and vastly investigated for genetics. Here, we combined the available phylogenetic data with information on niche divergence to explore the role of ecology into diversification at the species and gene pool levels.Key results – Ecological speciation through climate has probably played a key role in the evolution of the Erythrophleum species. The differential climatic niche of the species indicated adaptive divergence along rainfall gradients, that have probably been boosted by past climate fluctuations. At the gene pool level, past climate changes during the Pleistocene have shaped genetic diversity, though within Erythrophleum suaveolens, adaptive divergence also occurred.Conclusions – We believe that ecological speciation is a key mechanism of diversification for tropical African tree species, since such climatic niche partition exist among many other genera. Modelling the environmental niche of closely related taxa, and testing for niche differentiation, combined with divergence dates offered new insights on the process of diversification.